Mixing and air–sea buoyancy fluxes set the time-mean overturning circulation in the subpolar North Atlantic and Nordic Seas - Dafydd Gwyn Evans; N. Penny Holliday; Sheldon Bacon; Isabela Le Bras (Ocean Science, 2023)
The overturning streamfunction as measured at the OSNAP (Overturning in the Subpolar North Atlantic Program) mooring array represents the transformation of warm, salty Atlantic Water into cold, fresh North Atlantic Deep Water (NADW). The magnitude of the overturning at the OSNAP array can therefore be linked to the transformation by air–sea buoyancy fluxes and mixing in the region north of the OSNAP array. Here, we estimate these water mass transformations using observational-based, reanalysis-based and model-based datasets. Our results highlight that air–sea fluxes alone cannot account for the time-mean magnitude of the overturning at OSNAP, and therefore a residual mixing-driven transformation is required to explain the difference. A cooling by air–sea heat fluxes and a mixing-driven freshening in the Nordic Seas, Iceland Basin and Irminger Sea precondition the warm, salty Atlantic Water, forming subpolar mode water classes in the subpolar North Atlantic. Mixing in the interior of the Nordic Seas, over the Greenland–Scotland Ridge and along the boundaries of the Irminger Sea and Iceland Basin drive a water mass transformation that leads to the convergence of volume in the water mass classes associated with NADW. Air–sea buoyancy fluxes and mixing therefore play key and complementary roles in setting the magnitude of the overturning within the subpolar North Atlantic and Nordic Seas. This study highlights that, for ocean and climate models to realistically simulate the overturning circulation in the North Atlantic, the small-scale processes that lead to the mixing-driven formation of NADW must be adequately represented within the model's parameterisation scheme.

Arctic Ocean Boundary Exchanges: A Review - Sheldon Bacon; Alberto Naveira Garabato; Yevgeny Aksenov; Nicola Brown; Takamasa Tsubouchi (Oceanography, 2022)
The Arctic Ocean has long been—and to a large extent remains—a data-sparse region. Paucity of ocean and atmosphere measurements impacts the fidelity of atmospheric reanalyses, and ungauged rivers lead to uncertainties in measurement-based estimates of river runoff. However, there exists a data resource that can provide material help: sustained (long-term) ice and ocean measurements around the Arctic Ocean boundary. The Arctic Ocean is surrounded by land and connects to adjacent ocean basins via four main gateways: to the Pacific through Bering Strait, to the Atlantic through Davis Strait, and to the Nordic Seas via Fram Strait and the Barents Sea Opening. In addition, the Nordic Seas connect to the Atlantic across the Greenland-Iceland-Scotland Ridge, which has a substantial measurement history. Inverse methods combine these data sets to generate conservative velocity fields that are then used to generate estimates of surface fluxes of heat and freshwater as well as other quantities of interest, including net biogeochemical fluxes and (with other methods) estimates of ocean water transformation rates. Data resources are available to greatly extend the duration and the temporal resolution of present analyses.

Freshwater in the Arctic Ocean 2010–2019 - Amy Solomon; Céline Heuzé; Benjamin Rabe; Sheldon Bacon; Laurent Bertino; Patrick Heimbach; Jun Inoue; Doroteaciro Iovino; Ruth Mottram; Xiangdong Zhang; Yevgeny Aksenov; Ronan McAdam; et al. (Ocean Science, 2021)
The Arctic climate system is rapidly transitioning into a new regime with a reduction in the extent of sea ice, enhanced mixing in the ocean and atmosphere, and thus enhanced coupling within the ocean–ice–atmosphere system; these physical changes are leading to ecosystem changes in the Arctic Ocean. In this review paper, we assess one of the critically important aspects of this new regime, the variability of Arctic freshwater, which plays a fundamental role in the Arctic climate system by impacting ocean stratification and sea ice formation or melt. Liquid and solid freshwater exports also affect the global climate system, notably by impacting the global ocean overturning circulation. We assess how freshwater budgets have changed relative to the 2000–2010 period. We include discussions of processes such as poleward atmospheric moisture transport, runoff from the Greenland Ice Sheet and Arctic glaciers, the role of snow on sea ice, and vertical redistribution. Notably, sea ice cover has become more seasonal and more mobile; the mass loss of the Greenland Ice Sheet increased in the 2010s (particularly in the western, northern, and southern regions) and imported warm, salty Atlantic waters have shoaled. During 2000–2010, the Arctic Oscillation and moisture transport into the Arctic are in-phase and have a positive trend. This cyclonic atmospheric circulation pattern forces reduced freshwater content on the Atlantic–Eurasian side of the Arctic Ocean and freshwater gains in the Beaufort Gyre. We show that the trend in Arctic freshwater content in the 2010s has stabilized relative to the 2000s, potentially due to an increased compensation between a freshening of the Beaufort Gyre and a reduction in freshwater in the rest of the Arctic Ocean. However, large inter-model spread across the ocean reanalyses and uncertainty in the observations used in this study prevent a definitive conclusion about the degree of this compensation.

Atlantic Meridional Overturning Circulation: Observed Transport and Variability - Eleanor Frajka-Williams; Isabelle J. Ansorge; Johanna Baehr; Harry L. Bryden; Maria Paz Chidichimo; Stuart A. Cunningham; Gokhan Danabasoglu; Shenfu Dong; Kathleen A. Donohue; Shane Elipot; Patrick Heimbach; N. Penny Holliday; et al. (Frontiers in Marine Science, 2019)